2020
DOI: 10.1038/s41598-020-62429-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemo-magnetic field-photothermal breast cancer therapy based on porous magnetite nanospheres

Abstract: The efficacy of different modalities of treating breast cancer is inhibited by several limitations such as off-targeted drug distribution, rapid drug clearance, and drug resistance. To overcome these limitations, we developed Lf-Doxo-PMNSs for combined chemo-MF-PTT. The PMNSs were synthesized by hydrothermal method and their physicochemical properties were examined by FE-SEM, TEM, DLS, TGA, XRD investigations. The cytotoxicity of as-synthesized NPs against 4T1 cells was carried out by MTT and flow cytometry as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
13
37
0
Order By: Relevance
“…In addition to the release of Fe 2+ and H 2 S, Dox loaded on FeS-Dox@bLf NZs will be very effective on therapeutic activity. In agreement with the results of Singh, et al [51], Shari , et al [6], and Shari , et al [8] Fig. 2H shows that the release of Dox from FeS-Dox@bLf NZs increases with decreasing environmental acidity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to the release of Fe 2+ and H 2 S, Dox loaded on FeS-Dox@bLf NZs will be very effective on therapeutic activity. In agreement with the results of Singh, et al [51], Shari , et al [6], and Shari , et al [8] Fig. 2H shows that the release of Dox from FeS-Dox@bLf NZs increases with decreasing environmental acidity.…”
Section: Discussionsupporting
confidence: 91%
“…The physicochemical properties of FeS NZs were consistent with the ndings of Sathiyaraj and Thirumaran [38] and Yang, et al [39]. On the other hand, the results of SEM, TEM and FTIR similar to the outcomes of Shankaranarayanan, et al [40] and Shari , et al [8] showed that bLf and Dox were loaded on FeS NZs. Metallic NPs such as Fe, manganese (Mn), copper (Cu), etc.…”
Section: Discussionsupporting
confidence: 86%
“… [ 126 ] Mesoporous Fe 3 O 4 @SiO 2 NPs Mesoporous maghemite NPs DOX Combined DOX/magnetic/PTT therapy significantly inhibited growth and metastasis of breast cancer to lung while reduced cardiotoxicity. [ 127 , 128 ] GO@Fe 3 O 4 Nanocomposites DOX Increased cytotoxic efficacy to glioma cells. [ 129 ] Graphene nanosponge-supported lipid bilayer DTX PFH LF conjugation increased the tumor accumulation and penetration of NPs by increasing its bilayer fluidity.…”
Section: Preparation Techniques Of Lactoferrin Nanocarriersmentioning
confidence: 99%
“…Porous magnetic NPs showed excellent capacity of absorbing magnetic and optical wavelengths resulting in heat generation to kill cancer cells. Therefore, mesoporous Fe 3 O 4 @SiO 2 NPs (PMNSs) and maghemite NPs (MMNPs) were synthesized by hydrothermal method then chemically modified with Lf for tumor targeting and then physically loaded with DOX [ 127 , 128 ]. The combination of chemo- and photothermal/magnetic therapy showed enhanced antitumor efficacy.…”
Section: Preparation Techniques Of Lactoferrin Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation